ANALISIS SURVEI KEPUASAN MASYARAKAT MENGGUNKAN PENDEKATAN E-CRM (Studi Kasus : BP3TKI Lampung) - Ida Bagus Gede Sarasvananda; Choirul Anwar; Donaya Pasha; Styawati Styawati (Universitas Teknokrat Indonesia, 2021)
BP3TKI Lampung has a problem in the section regarding the Community Satisfaction Survey (SKM) activity, namely the data processing of the survey results must be calculated manually so it takes a long time. It is expected from this research how to build a web-based community satisfaction survey system, where this system can directly calculate and display the final results of the survey in the form of graphs. In this study, data collection methods were used in the form of interviews, observation, literature review, and documentation at the BP3TKI Lampung office. . The system design is carried out using a modeling language using UML. While the programming used is PHP using the MySQL database. And for the system development method in the form of Extreme Programming. There are four stages in extreme programming, namely planning (planning), design (design), coding (coding), and testing (testing). The final result of this design produces a web-based community satisfaction survey system for BP3TKI Lampung which is expected to make it easier for agencies to conduct surveys and calculate survey results more easily and quickly.Keyword: System, Survey, Satisfaction, Society.